Biological Assets Disclosure dan Faktor Faktor yang Mempengaruhi (Studi Pada Perusahaan Agrikultur yang Terdaftar Di BEI Periode 2017-2019) - Zulaika Putri Rokhimah; Ida Nurhayati (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
Companies engaged in agriculture have different assets compared to companies in other sectors and are only owned by companies in agriculture, namely biological assets. As a result of these unique and different biological asset characteristics, companies engaged in agriculture have the possibility to present information more biased when compared to companies engaged in other fields, especially in the measurement, presentation and disclosure of their fixed assets in the form of biological assets (Ridwan, 2011). This is not the optimal disclosure of biological assets in companies in the field of agriculture which is used as a writer to encourage re-examination of the problem of disclosure of biological assets.The samples are agricultural sector companies listed in Indonesia Stock Exchange (IDX) based on certain criteria, namely: Available complete financial statements that are published during the study period; and Companies that are consistently on the list of the Indonesia Stock Exchange and are not leaving and entering during the 2017-2019 period. The results reveals that KAP type variables affect Biological Asset Disclosure. While the intensity of biological assets, company size and profitability has not been proven to affect Biological Asset Disclosure.